About Delegated Legislation - Vladimir Valentinovich Kozhevnikov (SIASAT, 2022)
The problems of delegated lawmaking are considered. The author comes to the conclusion that if the domestic legal doctrine has a negative attitude to the problem of delegated legislation and there are very few examples of it, then in the countries of the Romano-Germanic and Anglo-Saxon legal families, legal science pays increased attention to this problem, and the role and importance, specific the weight of the right delegated in the system of sources of law is constantly increasing.